Utilizing the Value of Smart Sensor Data in Motor Manufacturing - Auranen, Vili (My University, 2022)
The topic of this master’s thesis was the utilizing of the value of smart sensor data in motor manufacturing at an electric motor factory in Vaasa. The target company has developed and manufactured smart sensors to customers for years and is now implementing them in its own production. In the thesis’s the possibilities of utilization of the data of smart sensor utilization in the Vaasa factory has been studied through a specified case study. The motors included in the pilot were selected by their usage in the process. The target was to identify improvement potentials for smart sensors in discrete industries and to create a plan for sensor data usage and further development. With the increased value of the efficient data usage, the target is to reduce unplanned stoppages, improve safety, and minimize the penalties and other costs paid because of delayed motors. An additional target was to improve the service and spare part activities with better utilization of data from the sensors as well as define the suitability of current motors in use to their current intended use. The concrete target of this thesis was to create reporting tools to the target company. First, a literature study was carried out for the basics in sensors, smart sensors, and electric motors. Special focus was on the target company’s smart motor sensors and their competitors on the market. With the information available the products were compared to each other. Conclusion were made on the basis of the pilot installation on the target factory’s premises on the value of the smart sensors on discrete production. Through the case study the additional value created to the target company of the smart sensor data was analyzed. A roadmap was created for the smart sensor data for further analyses, storing data and user experience. The outcome of this thesis was several Power BI templates, a fleet report and several recommendations for further development. Through a comparison it was noted that the ABB Ability Smart Sensor TM as a product is slightly more advanced than the smart sensors of the competitors. It was observed that only measuring the data does not bring value to the company, but the data has to be transformed into understandable and visual information and only after that it can bring real value to the company. In the case study it was also noted that actions based on the data created by the sensors can be performed in order to reduce unplanned outages in the motor manufacturing with the predictive data for timing of services and repairs. It was also observed that the data and information provided by the smart sensors can also be utilized in discrete manufacturing on motors that are not continuously used. This is additionally to the knowledge compared to the motors used in process industries where the value of the sensor data was already confirmed in earlier studies.

Diplomityön aiheena on kohdeyrityksen älykkään anturin tuottama lisäarvo yhtiön Vaasan moottoritehtaan moottorivalmistuksessa. Kohdeyritys on valmistanut älykkäitä antureita asiakkaille myytäväksi jo useita vuosia ja on nyt käyttöönottamassa tuotteen omassa prosessissaan. Työssä tutkitaan älykkään anturin tuottaman datankäytön mahdollisuuksia kohdeyrityksen Vaasan yksikössä, määritellyn pilotin avulla. Pilottiin valittiin moottorit käyttötarkoituksen mukaan. Tavoitteena on tunnistaa kehittämiskohteita älykkäälle sensorille kappaletavaratuotannossa sekä luoda suunnitelma sensoridatan käytölle ja sen kehittämiseen. Datan tehokkaan käytön tavoitteina on pienentää suunnittelemattomia käyttökatkoksia, parantaa työturvallisuutta ja minimoida moottorien viivästyneiden toimitusten aiheuttamat lisääntyneet rahti ja muut ylimääräiset kustannukset. Lisäksi datankäytön tuomalla lisäarvolla pyritään kehittämään huolto- ja varaosatoimintaa, sekä määrittelemään käytössä olevien moottorien soveltuvuus nykyiseen käyttötarkoitukseensa. Konkreettisena tavoitteena on luoda toimeksiantoyritykselle raportointityökaluja. Työ alussa on kirjallisuuskatsaus anturien, älykkäiden anturien ja sähkömoottoreiden perusteisiin. Erityisesti tarkasteltiin kohdeyrityksen älykkäitä antureita ja sen kilpailijoita. Näitä vertailtiin toisiinsa saatavilla olevan tiedon avulla. Älykkään anturin pilottiasennuksen perusteella tehtiin johtopäätöksiä antureiden soveltuvuudesta kappaletavaratuotantoon esimerkkiyrityksen kautta. Pilotin perusteella pyrittiin analysoimaan tuotteen käyttöönoton kannattavuutta kohdeyritykselle. Lopuksi luotiin tiekartta antureista saatavan datan analysoinnille, tallettamiselle ja esittämiselle. Työn tuloksena syntyi Power BI raportointipohjia ja fleet report sekä kehitysehdotuksia jatkotoimenpiteille. Lisäksi työssä havaittiin, että ABB:n Ability Smart Sensor TM on tuotteena kilpailijoitaan hieman edellä tuotteen ominaisuuksien ja käytettävyyden osalta. Työssä havaittiin, että pelkkä datan mittaaminen sensoreilla ei itsessään tuo lisäarvoa yritykselle, vaan data pitää muuttaa ymmärrettäväksi informaatioksi ja vasta sen jälkeen se tuo lisäarvoa kohdeyritykselle. Edellisten lisäksi pilotissa havaittiin, että anturien tuottaman datan perusteella voidaan tehdä toimenpiteitä, jotta tuotannon suunnittelemattomia katkoksia pystyttäisiin vähentämään käyttämällä Smart Sensorin tuottamia tietoja ennakoivien huoltojen ja korjausten ajastamisessa. Ilmi tuli myös, että Smart Sensoreiden tuottamaa dataa voi käyttää myös kappaletavarateollisuudessa käytössä olevissa moottoreissa, jotka eivät ole jatkuvassa käytössä. Näin on siis prosessiteollisuudessa jatkuvassa käytössä olevien moottorien lisäksi, jossa sensorien tuotta-man datan hyöty on vahvistettu jo aikaisemmin.
Keywords: sensors; production; electric motors; fi=Automaatio- ja tietotekniikka|en=Automation and Computer Science|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|